Assessment of Training Barriers Among Underserved Virginia Value-added Food Producers: A Proposed Structure for Improving Parity in Food Safety Educational Interventions - Katheryn Parraga; Liv Huselton; Mohamed Salem; Xinlei Zhang; Tiffany Drape; Chyer Kim; Alexis M. Hamilton (Journal of Food Protection)
Food manufacturing businesses, regardless of size, must comply with appropriate food safety education requirements, but guidance on effectively training small, minority-owned producers is lacking in key areas, such as preferred formats and knowledge of current perceived barriers to compliance. This study aimed to understand the greatest barriers to knowledge gain and behavior change for underserved value-added food producers in Virginia. An anonymous 10-question survey was administered to Virginia food producers through various channels, including email links, flyers, electronic tablets, or physical copies provided in person. The survey queried demographic information about the producer, factors that inhibited their learning, and suggestions for improved education and outreach. Responses (n = 124) were analyzed using descriptive statistics and logistic regression in RStudio version 4.2.3. The results indicated that many producers identify location as the primary barrier to attending and learning about food safety, followed by the frequency of available training events. Additionally, the three preferred learning tools for producers were factsheets, interactive sessions with trainers and/or materials, and prerecorded videos. While there is no single method to meet all the needs related to food safety training for small producers, it is crucial for Cooperative Extension to consider these factors when planning food safety training and workshops to ensure broader outreach to more producers to achieve parity in food safety education.